Environment acceptability as building material from organic contaminants leaching behavior in sludge - Mohd Kamil, Nor Amani Filzah; Roslee, Noor Faiza; Abdo Al-Khadher, Sadeq Abdullah (Springer, 2021)
Sludge is one of the major hazardous waste generated from industrial activities. Cost-effective remediation method and disposal has become the main issues worldwide. Many types of contaminants are produced from sludge, in which organic contaminants and heavy metals are the most toxic and concerned. Leaching heavy metals in solidification and stabilization (S/S) methods were mostly discussed in the literature and very limited to organic contaminants. This chapter focuses on building material’s environmental acceptability based on organic contaminants’ leaching behaviour in treated sludge by S/S method. The leaching during the use and the end of life phase is one of the issues in reusing the treated sludge. Studies on the potential sludge measurement as a raw material in the building material production are discussed further in this chapter. Specifically, types of organic contaminants in sludge, solidification and stabilization of organic contaminants from sludge and environment acceptability of sludge as building material are the subtopics in this chapter.